Phase transformations in binary colloidal monolayers1. Issue 12 (28th March 2015) - Yang, Ye; Fu, Lin; Marcoux, Catherine; Socolar, Joshua E. S.; Charbonneau, Patrick; Yellen, Benjamin B.
<x xml:space="preserve">Abstract</x> We have developed a magnetic colloidal system allowing for direct observations of crystal transformations in a binary alloy. Distinct modes for passing from a square checkerboard to a striped phase are observed for different orientations of the applied in-plane field relative to the crystal axes.